Empirical analysis of entrepreneurship and economic growth - Stel, André. (International studies in entrepreneurship ;, 2006)
Network Design and Management focuses on the latest methodological developments in three key areas---pricing of telecommunications services, network design, and resource allocation. These three elements are most relevant to current telecommunications planning. The first five chapters cover global deregulation of the telecommunications industry, effective pricing and revenue management, as well as an understanding of competitive pressures are key factors that will improve revenue in telecommunications companies. These chapters present some novel ideas related to pricing (including auction-based pricing of network bandwidth) and modeling competition in the industry. The next seven chapters outline what successful telecommunications companies of the future will need to do in order to minimize their costs and still meet customer expectations. In this context the optimal design/provisioning of telecommunication networks plays an important role. These chapters focus on network design for a wide range of technologies including SONET, SDH, WDM, and MPLS. They include the latest research developments related to the modeling and solving of network design problems. The final six chapters provide insightful solutions to several resource allocation problems. Day-to-day management/control of telecommunications networks is dependant upon the optimal allocation of resources. Pricing and Resource Allocation for Point-to-Point Telecommunication Services in a Competitive Market: A Bilevel Optimization Approach -- Pricing Analysis in International Interconnected Networks -- Modeling Competition among Wireless Service Providers -- A Supply Network of Oligopoly for the Advanced Intelligent Network -- A Network Provisioning Scheme Based on Decentralized Bandwidth Auctions -- An Optimization-Based Approach to Modeling Internet Topology -- Comparing Survivable Multi-Ring Configurations -- The Effect of Hop Limits on Optimal Cost in Survivable Network Design -- Compact Models for Hop-Constrained Node Survivable Network Design: An Application to MPLS -- A Note on Search by Objective Relaxation -- Minimizing the Number of Wavelength Conversions in WDM Networks with Hybrid Optical Cross-Connects -- An Uninformed Best First Search Based Wavelength Assignment Algorithm to Minimize the Number of Sonet ADMs in WDM Rings -- Distributed Control of Flow on Networks of General Topology -- A Combinatorial Approximation Algorithm for CDMA Downlink Rate Allocation -- Resource Allocation Model for Estimating Non-Uniform Spatial Loads in Cellular Wireless Networks -- Heavy Traffic Analysis of AIMD Models -- Unreliable Components with Fast Repair and Dynamic Network Restoration -- Multiple Service Classes for Rate Adaptive Streams.